Negative alcohol-related consequences experienced by young adults in the past 12 months: Differences by college attendance, living situation, binge drinking, and sex - Patrick, Megan E.; Terry-McElrath, Yvonne M.; Evans-Polce, Rebecca J.; Schulenberg, John E. (Addictive behaviors, 2020)
•Half of age 19/20 drinkers reported negative alcohol use consequences.•1/3 of non-binge and nearly 3/4 of binge drinkers reported negative consequences.•Vo-tech and 2-year college students reported more unsafe driving.•Negative consequences were more likely for women than men.•Negative consequences were less likely for those living with parents. This study estimated the prevalence of negative consequences associated with alcohol use in a national sample of young adults one or two years after graduating from high school, focusing on differences by college attendance, living situation, binge drinking, and sex. A subsample (N = 1068) of U.S. nationally representative Monitoring the Future study 12th grade students from 2006 to 2016 cohorts was followed-up at modal age 19 or 20 (in 2008–2017) and asked about negative consequences related to their own alcohol use during the past 12 months. Differences in prevalence were estimated and multivariable models examined associations with college attendance, living situation, binge drinking, and sex. Half of surveyed U.S. 19/20 year-old alcohol users (a third of non-binge drinkers and almost three-quarters of binge drinkers) experienced negative consequences in the past year. The likelihood of experiencing several consequence types was significantly associated with college attendance prior to controlling for living situation. In multivariable models controlling for living situation, unsafe driving due to drinking remained more likely for students attending 2-year colleges or vocational/technical schools than for 4-year college students or non-attenders. In general, negative consequence risk was elevated among young adults not living with parents (vs. those living with parents) and women (vs. men). Negative consequences from alcohol use are prevalent among young adults and differ by college attendance, living situation, binge drinking, and sex. Students at 2-year/vocational/technical schools are at particular risk for unsafe driving, warranting specific research attention and targeted intervention.